KAJIAN TINGKAT KERUSAKAN BIBIT ULIN (Eusideroxylon zwageri) PADA AREAL SHADE HOUSE DAN OPEN AREA DI PERSEMAIAN BALAI PERHUTANAN SOSIAL DAN KEMITRAAN LINGKUNGAN BANJARBARU - Siti Fadliatur Rahmi; Emmy Winarni; Susilawati Susilawati (Jurnal Sylva Scienteae, 2020)
Study of Damage level on Ulin Seedlings (Eusideroxylon zwageri) in the Shade House and Open area. This research was conducted in the Nursery of Balai Perhutanan Sosial dan Kemitraan Lingkungan  Banjarbaru. The objectives of this study was to analyze the frequency, intensity, and  damage level  caused by pests and diseases in the shade house and open area. The results showed the attack frequency of pest and disease were 38 seedling in the shade house and 49  in open area.  The attack intensity of pest and disease was 25% in the  shade house and 98% in open area. The level of damage of seedlings due to pest and disease attacks in the shade house were relatively light and in the open area were classified as moderateKeywords: Pest; Diseases; Ulin; Shade house; Open area